Platelet-derived bio-products: Classification update, applications, concerns and new perspectives. (February 2020) - Acebes-Huerta, Andrea; Arias-Fernández, Tamara; Bernardo, Ángel; Muñoz-Turrillas, María Carmen; Fernández-Fuertes, Judit; Seghatchian, Jerard; Gutiérrez, Laura
Abstract: Platelet derived bio-products in the form of platelet rich plasma, plasma rich in growth factors, or plasma-free platelet releasates, are being studied worldwide with the aim of proving their efficacy in tissue regeneration within many different clinical areas, such as traumatology, maxillofacial surgery, ophthalmology, dermatology and otorhinolaryngology, amongst others. The current lack of consensus in the preparation method and application form, or in the quality assessment of each bio-product, precludes adequate interpretation of the relevance of reported clinical outcomes, and, while many in clinicians are very positive about them, many are sceptic. Relevant aspects of these products are considered to propose a classification nomenclature which would aid a comprehensive comparison of clinical outcomes of bio-products of the same characteristics. Finally, the uses of platelet-derived bio-products in in vitro culture (for cell therapy purposes) as a substitute of animal-origin sera, and other future perspectives of applications of platelet-derived bio-products are discussed.